Positive correlation between body weight and body mass index with blood pressure in young adults - Yusni, Yusni; Rahman, Safrizal; Naufal, Iflan (Narra J, 2024)
Study assessing the correlation between body weight and body mass index (BMI) with blood pressure (DBP) in young adults is still limited. The aim of this The aim of the study was to investigate the link between body weight and BMI with blood pressure, as well as how much increasing body weight and BMI contribute to raising blood pressure in young men and women. A cross-sectional study was conducted among 1,107 young adults aged 18–22 years (women, n=705; men, n=402). Chi-squared test was used to assess the association between body weight and BMI with blood pressure. The Pearson correlation and linear regression analysis were used to determine the correlation and direction of the relationship between body weight and BMI with blood presure. Our data indicated associations between body weight and BMI with blood pressure (both had p=0.001). There was a strong significant correlation between body weight and systolic blood pressure (SBP) (r=0.709; p<0.001), whereas the correlation between body weight and diastolic blood pressure (DBP) was moderate (r=0.374; p<0.001). BMI moderately influenced SBP and DBP (r=0.488 and r=0.358; p<0.001). A linear correlation analysis revealed a positive association between body weight, BMI, and blood presure, where an increase in body weight of 1 kg results increase in SBP of 0.725 mmHg and DBP of 0.318 mmHg. In addition, an increase in BMI of 1 kg/m2 followed by an increase in SBP and DBP of 1.6 mmHg and 0.834 mmHg, respectively. This study highlights that nutritional status in young men and women is linked and has a positive correlation with blood pressure.